Predicting future left anterior descending artery events from non-culprit lesions: insights from the Lipid-Rich Plaque study . (19th August 2021) - Kuku, Kayode O; Garcia-Garcia, Hector M; Doros, Gheorghe; Mintz, Gary S; Ali, Ziad A; Skinner, William H; Artis, Andre K; ten Cate, Tim; Powers, Eric; Wong, Shing Chiu; Wykrzykowska, Joanna; Dube, Sandeep; et al.
Abstract: Aims: The left anterior descending (LAD) artery is the most frequently affected site by coronary artery disease. The prospective Lipid Rich Plaque (LRP) study, which enrolled patients undergoing imaging of non-culprits followed over 2 years, reported the successful identification of coronary segments at risk of future events based on near-infrared spectroscopy-intravascular ultrasound (NIRS-IVUS) lipid signals. We aimed to characterize the plaque events involving the LAD vs. non-LAD segments. Methods and results: LRP enrolled 1563 patients from 2014 to 2016. All adjudicated plaque events defined by the composite of cardiac death, cardiac arrest, non-fatal myocardial infarction, acute coronary syndrome, revascularization by coronary bypass or percutaneous coronary intervention, and rehospitalization for angina with >20% stenosis progression and reported as non-culprit lesion-related major adverse cardiac events (NC-MACE) were classified by NIRS-IVUS maxLCBI4 mm (maximum 4-mm Lipid Core Burden Index) ≤400 or >400 and association with high-risk-plaque characteristics, plaque burden ≥70%, and minimum lumen area (MLA) ≤4 mm 2 . Fifty-seven events were recorded with more lipid-rich plaques in the LAD vs. left circumflex and right coronary artery; 12.5% vs. 10.4% vs. 11.3%, P = 0.097. Unequivocally, a maxLCBI4 mm >400 in the LAD was more predictive of NC-MACE [hazard ratio (HR) 4.32, 95% confidence interval (CI) (1.93–9.69); P = 0.0004] vs. [HR 2.56, 95% CI (1.06–6.17); P = 0.0354] in non-LAD segments. MLA ≤4 mm 2 within the maxLCBI4 mm was significantly higher in the LAD (34.1% vs. 25.9% vs. 13.7%, P < 0.001). Conclusion: Non-culprit lipid-rich segments in the LAD were more frequently associated with plaque-level events. LAD NIRS-IVUS screening may help identify patients requiring intensive surveillance and medical treatment. Graphical Abstract: